Low-velocity impact of composite sandwich plate with facesheet indentation description - Drahman, Siti Hasyyati (Penerbit UTM Press, 2015)
Composite sandwich structures are applied in many engineering fields due to their high strength and stiffness but lightweight properties. There are currently not many studies that simultaneously consider both indentation and strain failure in the composite sandwich plate especially in presence of impact loading. Such knowledge is necessary to determine the facesheet strain after impact in order to find out whether the facesheet is totally failed as a result of indentation deformation. Hence, the purpose of this study is to model numerically the top facesheet indentation and strain failure of a fixed-end composite sandwich plate with honeycomb core when it is subjected to low-velocity impact at the center. The faceheets are made from Hercules AW193-PW prepreg consisting of AS4 fibers in a 3501-6 matrix (carbon/epoxy) with a stacking sequence of [0/90]. The honeycomb core is made from HRH 10 1/8-3.0 Nomex honeycomb (Ciba-Geigy). Type of the impactor used in this study is flat-ended cylinder, which is made from case-hardened steel. The composite sandwich plate is modeled as a two-dimensional problem with five and three degrees of freedom per node for the facesheets and honeycomb core, respectively. Only the stiffness matrix, [K], and the mass matrix, [M], are considered in determining the responses of the plate. Responses in terms of indentation, strain failure and displacement are explored for various facesheet and core properties. It is found that an increase in number of ply and ply thickness reduce the indentation on the top facesheet. Also, the most effective parameter in improving the strain failure of the top facesheet is the crushing resistance of the core.